ANALYSIS OF CUSTOMER SATISFACTION AND VALUE OF THE MINERAL WATER PRODUCTS IN SOUTH SOLOK DISTRICT - Rubianto Pitoyo (Jurnal Apresiasi Ekonomi, 2018)
The purpose of this research is to know analyze the influence of product service to customer satisfaction of mineral water product. Technique of taking data using questionnaire with 12 item question for product service variable, and 12 item question for customer satisfaction variable filled by 50 respondents. The questionnaire first tested its validity and reliability. Technical data analysis techniques using descriptive analysis, and customer value analysis. A customer will feel satisfied or be loyal to the company due to the receipt of more services, in addition to satisfied with the quality of products purchased. Product service is one form of producer strategy to provide customer satisfaction. Product service strategy through product differentiation strategy is aimed at obtaining high customer value or achieving customer satisfaction. A customer value is a ratio of the benefits the customer receives and the sacrifice of the producer's costs to provide additional services. Based on the results of descriptive analysis it is known that the level of respondents 'achievement of product service variables is quite good, and the level of respondents' achievement of customer satisfaction is quite good. From the result of inductive analysis, it is known that there are t-hitung variable of product service to customer satisfaction equal to (6,799)> t-table (1,7011), this regression model explains that product service have positive and significant effect to customer satisfaction of mineral water product. From the measurement result of customer value it can be seen that customer value is equal to 1.62, which means customer is more concerned with service to achieve satisfaction.Keyword: Product service, Customer satisfaction, Customer Value